Pendampingan Belajar Pecahan Sederhana Melalui Media Puzzle Pecahan Di Rumah Baca Hasan-Savvas Kota Lhokseumawe - Iryana Muhammad; Mutia Fonna (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The use of media becomes one of the components in learning and helps teachers to realize student-centered learning. In fact, many students at the Hassan-Savvas Reading House do not understand the material, especially fractions, because not every school uses learning media, this is also the background in doing community service. The purpose of this service is to provide assistance in learning mathematics on simple fraction material in an interesting way, namely through the media of Fractional Puzzles. The participants were 15 elementary school level children who lived around Rumoh Baca Hasan Savvas in Gampong Jambo Timu, Blang Mangat District, Lhokseumawe City. The method used is socialization, discussion, practice questions and discussion. The results of the mentoring show that in each learning the participants look happy, active and pay attention to the discussion of the Fractional Puzzle media. Participants are interested in compiling puzzles, so that it has an impact on increasing knowledge of Fractions material. Increased knowledge can be seen from the acquisition of the N-Gain value of 84% with the High criteria. The results of the assistance show an increase in knowledge of fractions through the Fractional Puzzle media